Transplantation of expanded criteria kidney grafts to elderly recipients in the N.V. Sklifosovsky Research Institute for Emergency Medicine - N. V. Shmarina (Transplantologiâ, 2018)
Introduction: The expansion of the criteria for donor organ retrieval contributes to an increase in the number of kidney transplantations to elderly recipients; but in view of reduced requirements to donor organ quality, a further analysis of transplantation outcomes is needed. The aim was to analyze and compare the outcomes of kidney transplantation to elderly patients depending on the donor organ quality.Material and methods. The study was based on the analysis of the kidney transplantation outcomes in 61 elderly recipients, including 51 transplantations performed from expanded criteria donors (group 1), and other 10 from standard donors (group 2). Based on clinical, laboratory, histological, and instrumental diagnostic data, we compared the graft function recovery rates, graft/recipient survival rates, the causes of graft loss in the early posttransplant period.Results: Patients of group I had significantly higher delayed graft function rates (37.3% vs. 10%), graft non-function rates (15.7% vs. 0%), and lower early posttransplant survival rates (72.5% vs. 100%). Graft function recovery rate was 58.8% in group I, and 100% in the patients of group II. The most common cause of the graft loss and the renal graft removals performed in the early posttransplant period was the poor graft quality due to the donor's existing pathology.Conclusion. The study demonstrated a statistically significant deterioration of the initial graft function, significantly increased graft non-function rates, and decreased graft survival rates in the early posttransplant period in the elderly recipients after kidney transplantation from expanded criteria donors.